THE NEXUS OF PLANNING AND FOOD SECURITY IN INDONESIA: A REVIEW OF THE LITERATURE - Sri Tuntung Pandangwati; Dodi Widiyanto (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2023)
This review paper draws on a multidisciplinary body of literature to consider how planning can foster food security in Indonesia. In the last decades, the international planning discourse has been increasingly attentive to a range of food security issues such as food deserts, urban agriculture, rural agricultural land conservation and resilient food systems. The existing studies mainly explore how planning can be more sensitive to food issues. However, to what extent Indonesian studies are attentive to the intersection of food and planning has not been clarified yet. This paper addresses this gap by reviewing 38 published studies in Indonesia to investigate how the existing studies in Indonesia link food security with planning. Food, as one of three primary needs, should be the concern of planners, especially in this era of uncertainties and global environmental change. Establishing food security should involve multidisciplinary research, including planning which can potentially contribute to managing the spatial dimensions of food production, distribution and utilisation.